Effects of various compounds on the biological performance of the THIOPAQ® reactor and start-up and stabilization of an ANAMMOX® lab-scale reactor - Pinto, José Filipe Carvalho (2018)
Dissertação de mestrado em Tecnologia e Ciência Alimentar